Ice Engineering - Tensile Properties of Sea Ice Grown in a Confined System. - Dykins, J. E. (1970)
Tensile strength envelopes were developed for horizontally and vertically oriented specimens of saline ice. The upper boundary limit in each case represents 1- to 2-ppt salinity ice for temperature range -4C to -27C, while the lower boundary represents 7- to 9-ppt salinity ice for the same temperature. The salinity, density, and petrographic structure of the 7- to 9-ppt natural seawater ice, which was grown in the laboratory, are closely identifiable with the characteristics of sea ice formed in a natural environment. This observation was based on comparison of the upper 44 cm of laboratory ice with a similar thickness of natural sea ice. The tensile strength was found to be a nonlinear function of temperature; there were strong implications, however, that a linear relationship with salinity may exist. The strength was found to be dependent on orientation of the stress field with both the grain (crystal) and subgrain (platelet) structure. Limited study indicates that the tensile strength of saline ice is appreciably reduced as stress rates increase above 25 psi/sec. (Author)